Effects of the Argon Pressure on the Optical Band Gap of Zinc Oxide Thin Films Grown by Nonreactive RF Sputtering - M. Acosta; I. Riech; E. Martín-Tovar (Advances in Condensed Matter Physics)
Zinc oxide (ZnO) thin films were grown by nonreactive RF sputtering at room temperature under varying argon pressures (PAr). Their optical band gap was found to increase from 3.58 to 4.34 eV when the argon pressure increases from 2.67 to 10.66 Pa. After annealing at 200°C and 500°C, optical band gaps decrease considerably. The observed widening of the band gap with increasing PAr can be understood as being a consequence of the poorer crystallinity of films grown at higher pressures. Measurements of morphological and electrical properties of these films correlate well with this picture. Our main aim is to understand the effects of PAr on several physical properties of the films, and most importantly on its optical band gap.